Potestad Sancionadora Administrativa en Materia de Salud - Quijano Caballero, Oscar Ítalo (2015)
In the first part of this article develops concepts and policy aspects of the right to health, in order to reveal the nature of the interference of the State in the field of health and the content of the law that aims to protect and restore with the exercise of administrative powers to impose penalties; also formulates a brief overview of health reform in the Peru, undertaken with the package of legislative decrees issued by the Executive, published between September 12 and December 07, the year 2013, in accordance with the powers conferred by the legislature through the law N ° 30073, in order to explain the context in which was given powers to impose penalties in the field of health the national Superintendence of health (SUSALUD).The central aspect of the proposal is the administrative penalties procedure for SUSALUD: its background, actors, structure, infractions, sanctions, interim measures and corrective measures; finally, a few lines are dedicated to the transfer of the competence to protect the rights of consumers of health services of INDECOPI to SUSALUD.